Personality development from college to midlife: A cross-cultural comparison - McCrae, R.R (Array, 1997)
Although personality is generally stable after age 30, both cross-sectional and longitudinal studies in the United States have shown consistent changes between college age and middle adulthood. There appear to be declines in three of the Big Five factors of personality - Neuroticism, Extraversion and Openness- and increases in Agreeableness and Conscientiousness. These changes might be unique to the experience of late adolescence in the United States. To examine cross-cultural generalizability of these findings, the Revised NEO Personality Inventory was administered to samples in Korea, Italy, and Croatia (Ns = 448 -716). The same general pattern of age differences was seen in each country, for both males and females. Results are consistent with the hypothesis that these are universal maturational changes in personality.